PENGARUH MOTIVASI BELAJAR, FASILITAS,PERCEIVED CONTROL DAN MODEL PEMBELAJARAN TERHADAP PRESTASI MAHASISWA PROGRAM STUDI AKUNTANSI UNIVERSITAS SYIAH KUALA - Safira, Ulfa; Fuadi, Raida (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
The purpose of this study is to determine and analyze the influence of learning motivation, facilities, perceived control, and learning model of educator accountants on the achievement of accounting students of the Shia Kuala University. The sample taken in this study is probability sampling with random sampling method. The number of samples used in this study were 200 respondents. The data obtained were analyzed by using Linear Regression Analysis with SPSS IMB Ver 22 program. The results of this research indicate that variables of learning motivation, facilities, perceived control, and learning models has positively significant impact to student achievement.